Sentencing reforms and the War on Drugs: an analysis of sentence outcomes for narcotics offenders adjudicated in U. S. District Courts on the Southwest border - Hartley, Richard D. (Journal of contemporary criminal justice, 2008)
Sentencing reforms and the war on drugs have greatly changed the landscape of federal sentencing and the composition of the federal prison population. As of 2006, 56% of federal prison inmates were incarcerated for narcotics offenses. The Sentencing Reform Act of 1984, the United States Sentencing Commission Guidelines, and mandatory minimum statutes were all enacted in an attempt to make sentences more proportional, more uniform, and less disparate. More than 35 years have passed since reform began, and still there are questions about whether unwarranted disparities have been eliminated from the system and whether punishments are more proportional and uniform. Another question that has recently surfaced is whether one unitary federal law can produce uniform sentencing practices because of variations that exist at the district level. This research analyzes the decision-making practices of judges for narcotic violations in four districts in the southwestern United States. The purpose of this study is to illustrate that even in districts that have similar types of cases and political agendas regarding narcotics offending, interdistrict variation in the factors that affect sentencing outcomes still exist.